The Effect Of Shape And Weight Towards The Performance Of Simple Adaptive Median Filter In Reducing Impulse Noise Level From Digital Images. - Sia, Nicholas Pik Kong; Ibrahim, Haidi (2010)

(untitled)
Recently, Simple Adaptive Median (SAM) filter has been introduced for the purpose of reducing the impulse noise level in digital images.